Decision and Horizon Rules for Stochastic Planning Problems: A Linear Example - Charnes, Abraham; Dreze, Jacques; Miller, Merton (Econometrica, 1966)
Analytic decision rules and horizon rules are developed for the warehousing problem. A stochastic warehousing problem is defined and solved, first by backwards induction, then by means of a forward working algorithm. The influence of holding costs and discount rates on forecasting horizons is illustrated.